ILMU RASM QURAN - Mira Shodiqoh (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2019)
The science of rasm of the Al-Qur’an is the study of the writing of the mushaf of the Al-Qur’an which is carried out in a special way, both in the writing of the pronunciations and the forms of letters used. Writing of the Al-Qur’an during the time of the Prophet Muhammad. Performed by his friends both in writing and in order with the aim to unite the Muslims in one type of Manuscripts by uniforming the reading and unifying the orderly arrangement of the verses. Thus there is no difference in understanding between the Manuscripts with other Manuscripts.